Gomphrena claussenii, a novel metal‐hypertolerant bioindicator species, sequesters cadmium, but not zinc, in vacuolar oxalate crystals. Issue 3 (17th June 2015) - Villafort Carvalho, Mina T.; Pongrac, Paula; Mumm, Roland; van Arkel, Jeroen; van Aelst, Adriaan; Jeromel, Luka; Vavpetič, Primož; Pelicon, Primož; Aarts, Mark G. M.
Summary Gomphrena claussenii is a recently described zinc (Zn)‐ and cadmium (Cd)‐hypertolerant Amaranthaceae species displaying a metal bioindicator Zn/Cd accumulation response. We investigated the Zn and Cd distribution in stem and leaf tissues of G. claussenii at the cellular level, and determined metabolite profiles to investigate metabolite involvement in Zn and Cd sequestration. Gomphrena claussenii plants exposed to high Zn and Cd supply were analysed by scanning electron microscopy with energy‐dispersive X‐ray (SEM‐EDX) and micro‐proton‐induced X‐ray emission (micro‐PIXE). In addition, gas chromatography‐time of flight‐mass spectrometry (GC‐TOF‐MS) was used to determine metabolite profiles on high Zn and Cd exposure. Stem and leaf tissues of G. claussenii plants exposed to control and high Cd conditions showed the abundant presence of calcium oxalate (CaOx) crystals, but on high Zn exposure, their abundance was strongly reduced. Ca and Cd co‐localized to the CaOx crystals in Cd‐exposed plants. Citrate, malate and oxalate levels were all higher in shoot tissues of metal‐exposed plants, with oxalate levels induced 2.6‐fold on Zn exposure and 6.4‐fold on Cd exposure. Sequestration of Cd in vacuolar CaOx crystals of G. claussenii is found to be a novel mechanism to deal with Cd accumulation and tolerance.